PENGEMBANGAN MEDIA KARTU PINTAR UNTUK MEMBACA AWAL ANAK USIA 4-5 TAHUN DI TK ISLAM AL- ARIF - Noventa Desyana; Mutiara Sari Dewi; Ari Kusuma Sulyandari (Jurnal Dewantara, 2022)
The researcher raised the title "Development of Smart Card Media for Early Reading for 4-5 Years Old Children at Al-Arif Islamic Kindergarten." Aims to be a solution to problems that occur to children who are still confused in early reading skills such as recognizing initial letters, colors, and reading images through smart card development media. The type of research used by the researcher is the development of qualitative and quantitative research with R&D (Research and Development) and data collection using interviews, observations, questionnaires, and documentation at the Al- Arif Islamic Kindergarten, Mulyorejo Village, Sukun District, Malang Regency. The results of research at Al-Arif Islamic Kindergarten on the development of smart card media on initial letter recognition activities, colors, and reading images with a score of 76% to 100% so that it can be determined that smart card media is good and suitable for use in early reading activities. children aged 4-5 years at Al-Arif Islamic Kindergarten, Mulyorejo Village, Sukun District, Malang Regency